The Orientation of Visual Space from the Perspective of Hummingbirds - Tyrrell, Luke P.; Goller, Benjamin; Moore, Bret A.; Altshuler, Douglas L.; Fernández-Juricic, Esteban (Frontiers in Neuroscience, 2018)
Vision is a key component of hummingbird behavior. Hummingbirds hover in front of flowers, guide their bills into them for foraging, and maneuver backwards to undock from them. Capturing insects is also an important foraging strategy for most hummingbirds. However, little is known about the visual sensory specializations hummingbirds use to guide these two foraging strategies. We characterized the hummingbird visual field configuration, degree of eye movement, and orientation of the centers of acute vision. Hummingbirds had a relatively narrow binocular field (~30°) that extended above and behind their heads. Their blind area was also relatively narrow (~23°), which increased their visual coverage (about 98% of their celestial hemisphere). Additionally, eye movement amplitude was relatively low (~9°), so their ability to converge or diverge their eyes was limited. We confirmed that hummingbirds have two centers of acute vision: a fovea centralis, projecting laterally, and an area temporalis, projecting more frontally. This retinal configuration is similar to other predatory species, which may allow hummingbirds to enhance their success at preying on insects. However, there is no evidence that their temporal area could visualize the bill tip or that eye movements could compensate for this constraint. Therefore, guidance of precise bill position during the process of docking occurs via indirect cues or directly with low visual acuity despite having a temporal center of acute vision. The large visual coverage may favor the detection of predators and competitors even while docking into a flower. Overall, hummingbird visual configuration does not seem specialized for flower docking.